Reconfigured and Notched Tapered Slot UWB Antenna for Cognitive Radio Applications. (27th November 2012) - Aboufoul, Tamer; Alomainy, Akram; Parini, Clive
Abstract : A compact reconfigurable and notched ultra-wideband (UWB) tapered slot antenna (TSA) is presented. The antenna reconfiguration operation principle relies on 2 mechanisms: in the first mechanism a resonator parasitic microstrip line electrically coupled to the TSA is used to notch the TSA at a specific frequency and the second mechanism relies on changing the input impedance matching of the antenna by means of changing the length of a stub line extended from an additional tiny partial ground on the back side of the antenna. The reflection coefficient, radiation patterns, and gain simulations and measurements for the proposed antenna are presented to verify the design concepts featuring a very satisfactory performance. Total efficiency simulations and measurements are also presented to highlight the filtering performance of the reconfigured antenna. When the antenna was reconfigured from the UWB to work into multiple frequency bands, the radiation patterns were still the same and the total peak gain has slightly improved compared to the UWB case. In addition, when the antenna operated in the notched mode, the gain has significantly dropped at the notch frequency. The simplicity and flexibility of the proposed multimode antenna make it a good candidate for future cognitive radio front ends.